2005
DOI: 10.1093/sw/50.1.31
|View full text |Cite
|
Sign up to set email alerts
|

Place First, Then Train: An Alternative to the Medical Model of Psychiatric Rehabilitation

Abstract: The medical model has promoted a train-place model for psychiatric rehabilitation. This model carefully trains people with psychiatric disabilities on a range of skills so they can handle real-world demands before placing them in work and independent living situations. More consistent with a social work perspective are place-train programs, which rapidly place people with psychiatric disorders in real-world settings so they can experience the benefits, as well as the challenges of these situations, and then pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0
5

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(45 citation statements)
references
References 54 publications
1
39
0
5
Order By: Relevance
“…These findings can perhaps be explained by the IPS-participants training and gradually developing their social skills at work, a so called place-then-train approach (10,39), instead of participating in traditional prevocational rehabilitation in sheltered settings. However, limitations in work performance caused by cognitive limitations is assumed to remain stable over time (40), which may help to explain why cognitive limitations were perceived as enduring or gradually increasing among the study participants.…”
Section: Discussionmentioning
confidence: 99%
“…These findings can perhaps be explained by the IPS-participants training and gradually developing their social skills at work, a so called place-then-train approach (10,39), instead of participating in traditional prevocational rehabilitation in sheltered settings. However, limitations in work performance caused by cognitive limitations is assumed to remain stable over time (40), which may help to explain why cognitive limitations were perceived as enduring or gradually increasing among the study participants.…”
Section: Discussionmentioning
confidence: 99%
“…The mental health field appears to be in the grips of conflicting and competing paradigms (Corrigan & McCracken, 2005;Rinaldi et al, 2008). There has long been a biomedical-oriented perspective that uses a "train then place" model, with the expected trajectory being: "The illness is decisive for first care, then treatment, and later on rehabilitation, and possibly vocational rehabilitation" (Bejerholm, Larsson, & Hofgren, 2011, p. 60).…”
Section: Conflicting Paradigmsmentioning
confidence: 99%
“…While the medical model seeks to train those diagnosed with mental illness to manage their condition before giving them work and accommodation (the "train-place" model), the "place-train" model instead quickly places them in work and accommodation, then gives them training and support (Corrigan and McCracken 2005). Most studies of the "place-train" model have so far shown greater success in helping those diagnosed with mental illness to live independently (e.g., with greater housing stability and quality of life), as well as greater reduction in rehospitalisation rates (Corrigan and McCracken 2005). Thus, even if the issue here is a mental illness, these findings challenge the medical model's emphasis on medication as the first and most important aspect of recovery.…”
Section: The Danger Of Inappropriate Treatmentmentioning
confidence: 99%